The Human Adenovirus Type 5 E4orf6/E1B55K E3 Ubiquitin Ligase Complex Enhances E1A Functional Activity - Dallaire, Frédéric (mSphere, 2015)
Human adenovirus (Ad) E1A proteins have long been known as the central regulators of virus infection as well as the major source of adenovirus oncogenic potential. Not only do they activate expression of other early viral genes, they make viral replication possible in terminally differentiated cells, at least in part, by binding to the retinoblastoma (Rb) tumor suppressor family of proteins to activate E2F transcription factors and thus viral and cellular DNA synthesis. We demonstrate in an accompanying article (F. Dallaire et al., mSphere 1:00014-15, 2016) that the human adenovirus E3 ubiquitin ligase complex formed by the E4orf6 and E1B55K proteins is able to mimic E1A activation of E2F transactivation factors. Acting alone in the absence of E1A, the Ad5 E4orf6 protein in complex with E1B55K was shown to bind E2F, disrupt E2F/Rb complexes, and induce hyperphosphorylation of Rb, leading to induction of viral and cellular DNA synthesis, as well as stimulation of early and late viral gene expression and production of viral progeny. While these activities were significantly lower than those exhibited by E1A, we report here that this ligase complex appeared to enhance E1A activity in two ways. First, the E4orf6/E1B55K complex was shown to stabilize E1A proteins, leading to higher levels in infected cells. Second, the complex was demonstrated to enhance the activation of E2F by E1A products. These findings indicated a new role of the E4orf6/E1B55K ligase complex in promoting adenovirus replication. IMPORTANCE Following our demonstration that adenovirus E3 ubiquitin ligase formed by the viral E4orf6 and E1B55K proteins is able to mimic the activation of E2F by E1A, we conducted a series of studies to determine if this complex might also promote the ability of E1A to do so. We found that the complex both significantly stabilizes E1A proteins and also enhances their ability to activate E2F. This finding is of significance because it represents an entirely new function for the ligase in regulating adenovirus replication by enhancing the action of E1A products.